Kinetic and Thermodynamic Studies on Removal of Selenium from Aqueous Solution by Using Nano-TiO2 - Huang, Ting (Asian Journal of Chemistry, 2012)
A novel sorbent, nano-TiO2 was employed for the removal of selenium from aqueous solution in batch equilibrium experiments, in order to investigate its adsorption properties. The removal percentage of selenium by the sorbent increased with increasing pH in the acidic medium. The adsorption capacities and removal percentage of Se(IV) onto nano-TiO2 were evaluated as a function of the solution concentration and temperature. The sorption of Se(IV) ions onto nano-TiO2 followed the second-order rate equation and the Langmuir model could describe the adsorption of nano-TiO2 to Se(IV) ions successfully over the whole range of concentration studied. The value of standard enthalpy and standard entropy (DHº, DSº > 0) may be interpreted as the endothermic adsorption process. The negative value of DGº showed the adsorptions of Se(IV) by nano-TiO2 were a spontaneous process.